Pengembangan Media Diorama Berbasis Literasi Sosial untuk Meningkatkan Hasil Belajar pada Mata Pelajaran IPAS Kelas V Sekolah Dasar - Fina Khoirun Nihayati; Wahyu Nugroho; Intan Susetyo Kusumo Wardhani (Mataram University, 2026)
Learning on the topics of production, distribution, and consumption in elementary schools is still dominated by conventional teaching methods and limited learning media, resulting in low student engagement, inadequate social literacy, and unsatisfactory learning outcomes. Since these topics are closely related to students' social interactions and everyday economic activities, learning media that integrate social literacy are needed to promote meaningful learning experiences. This study aimed to develop social literacy-based diorama media and to determine its feasibility, practicality, and effectiveness in improving the IPAS (Natural and Social Sciences) learning outcomes of fifth-grade elementary school students. The study employed the Research and Development (R&D) method using the ADDIE model, which comprises the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 39 fifth-grade students from SDN 1 Kerjo, SDN 3 Kedungsigit, and SDN 3 Jatiprahu in Trenggalek Regency. Data were collected through observation, interviews, questionnaires, documentation, and tests. The results showed that the media received validation percentages of 87% from subject matter experts, 78% from linguists, 80% from media experts, and 87% from practitioners, placing it in the